A Pre-Service Teacher Experiences of Creating Vocabulary Quizzes for EFL Adult Learners: the ACTIONS Model - Istiqomatul Faizah; Nur Arifah Drajati; Melor Md. Yunus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sebelas Maret, Indonesia, 2022)
IDLE (Informal Digital Learning of English) is a worldwide phenomenon that represents one of the most significant advances in autonomous language learning outside the classroom in recent decades. This study examines the experiences of IDLE activities based on the ACTIONS model (Access, Cost, Teaching and learning, Interactivity and user-friendliness, Organizational issues, Novelty, and Speed) which focused on vocabulary. The results of the study are intended to be a self-reflection on the factors involved in creating English vocabulary quizzes on Instagram as IDLE sources for higher education students. The study aims to use social media, especially Instagram, as a learning tool in a digital context. The researcher uses written narratives that contain her experiences in creating such English vocabulary quizzes. For that reason, the study participant is the researcher herself, a 21-year-old female undergraduate student in the English Education Department. In the study, the researcher uses thematic analysis to analyse the narrative data. This includes three activities: 1) repeated reading of the data; 2) coding and categorising the data extracts; and 3) recognising the thematic headings. The results show that creating IDLE activities based on the ACTIONS model leads to flexibility of access, affordable costs, teaching and learning needs based on followers' feedback and correction, excellent interactivity and user-friendliness, no organisational issues, novelty, and speed. The study offers new insights into how English pre-service teachers' engagement with IDLE serves as a significant factor in their future teaching tasks.